Pre-Service English Teachers’ Digital Pedagogy Development through Project-Based Learning in TEFL Classrooms - Samsidaris; Restu Januarty Hamid; Areski Wahid; Farida (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This qualitative descriptive study investigates how Project-Based Learning (PjBL) supports pre-service English teachers’ digital pedagogy development in a TEFL classroom. Although previous studies have examined technology integration and digital competence in teacher education, limited attention has been given to how pre-service teachers develop pedagogical reasoning while designing digital English teaching media through project-based experiences. This study involved 20 sixth-semester students in the English Education Study Program, Faculty of Education and Literature, Universitas Bosowa, Indonesia. Data were collected through classroom observations, semi-structured interviews, reflective journals, and documentation of students’ digital teaching media projects. The data were analyzed using thematic analysis to identify patterns related to learning experiences, digital media development, collaboration, reflection, and challenges. The findings reveal that PjBL functioned as a bridge between TEFL theory and teaching practice by encouraging students to transform pedagogical concepts into meaningful digital learning resources. The project supported the development of pedagogical creativity, technology-informed instructional decision-making, collaboration, and reflective awareness as future English teachers. The findings also indicate that students gradually shifted from focusing on digital tools as products toward understanding technology as a means to achieve learning objectives. However, students experienced challenges related to technical skills, pedagogical alignment, and time management. The study contributes to TEFL teacher education by demonstrating how PjBL can foster digital pedagogy development through the integration of theory, practice, technology, and reflection. Practically, the findings suggest that TEFL lecturers should provide structured guidance, feedback, and reflective activities to help pre-service teachers design pedagogically meaningful digital teaching media.